A comprehensive numerical chronology for the pre-Columbian cultures of the Palpa valleys, south coast of Peru - Unkel, Ingmar; Reindel, Markus; Gorbahn, Hermann; Isla, Johny; Kromer, Bernd; Sossna, Volker (Journal of archaeological science, 2012)
Before the arrival of the Spaniards in Peru in 1532, many different societies flourished in the coastal desert of southern Peru. Of these, one of the best known is the Nasca culture (living in the area between about 260 cal BC and 640 cal BC.), which created the famous geoglyphs on the desert floor. In this paper we present a numerical chronology for the cultural development in the valleys of Palpa, in the northern part of the Nazca region, which spans the time from the Archaic Period (starting there around 3760 cal BC) to the Late Intermediate Period (terminating with the arrival of the Spaniards in 1532 AD). The chronology is based on more than 150 14C samples collected by our project from well-documented archaeological excavations of 17 different sites in and around Palpa. Thanks to the advanced AMS-14C dating technique, demanding only few milligrams of organic material, we could focus on samples of plants, like beans, corn, or reed, representing single years of growth or use, and also on delicate materials like straw from clay bricks (adobe) and textiles. All single 14C dates were combined to cultural phases using a Bayesian statistical model, implementing the a priori information of the archaeological contexts, and adopting the relative ceramic chronologies available for this area.
Gesehen am 19.02.2025
Online veröffentlicht: 3. März 2012